Evaluation of optical coherence tomography findings in age-related macular degeneration: a reproducibility study of two independent reading centres. Issue 3 (30th August 2010) - Ritter, Markus; Elledge, Julee; Simader, Christian; Deak, Gabor G; Benesch, Thomas; Blodi, Barbara A; Schmidt-Erfurth, Ursula M
Abstract : Background/aims: To determine the reproducibility among readers of two independent certified centres, the Vienna Reading Center (VRC) and the University of Wisconsin-Madison Reading Center (UW-FPRC) for optical coherence tomography (OCT) images in age-related macular degeneration (AMD). Methods: Fast macular thickness scans and 6 mm cross hair scans were obtained from 100 eyes with all subtypes of AMD using Stratus OCT. Consensus readings were performed by two certified OCT readers of each reading center using their grading protocol. Common variables of both grading protocols, such as presence of cystoid spaces, subretinal fluid, vitreomacular traction and retinal pigment epithelial detachment, were compared using κ statistics. In addition, the intraclass correlation coefficient (ICC) was calculated for centre point thickness (CPT) of values re-measured manually in the presence of alignment errors. Results: The reproducibility was dependent on the variable measured with a κ value of 0.81 for the presence of cystoid spaces, 0.78 for the presence of subretinal fluid and 0.795 for the presence of vitreomacular traction. The lowest reproducibility was found for the presence of retinal pigment epithelial detachment with a κ value of 0.51. The CPT was re-measured in 29 out of 100 scans at both sites with an ICC of the re-measured thicknesses of 0.92. Conclusion: OCT scan data are crucial in monitoring treatment efficacy in AMD clinical trials. For comparison of results obtained by different reading centers, the inter-reading center reproducibility is essential. Although the reproducibility is generally high, the reliability depends on the selected morphological parameters.